2017
DOI: 10.1093/mnras/stx2885
|View full text |Cite
|
Sign up to set email alerts
|

Disc–corona interaction in the heartbeat state of GRS 1915+105

Abstract: Timing analysis provides information about the dynamics of matter accreting on to neutron stars and black holes, and hence is crucial for studying the physics of the accretion flow around these objects. It is difficult, however, to associate the different variability components with each of the spectral components of the accretion flow. We apply several new methods to two Rossi X-ray Timing Explorer observations of the black hole binary GRS 1915+105 during its heartbeat state to explore the origin of the X-ray… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 85 publications
1
2
0
Order By: Relevance
“…thors found that the frequency of the QPO increases up to 3-4 keV and above that energy the frequency increases very slowly. A similar behaviour was observed in observations of some of the classes of GRS 1915+105 (Qu et al 2010;Yan et al 2012Yan et al , 2018.…”
Section: Energy Dependence Of the Fwhm Of 𝐿 𝑙supporting
confidence: 87%
See 1 more Smart Citation
“…thors found that the frequency of the QPO increases up to 3-4 keV and above that energy the frequency increases very slowly. A similar behaviour was observed in observations of some of the classes of GRS 1915+105 (Qu et al 2010;Yan et al 2012Yan et al , 2018.…”
Section: Energy Dependence Of the Fwhm Of 𝐿 𝑙supporting
confidence: 87%
“…There are other BH LMXBs in which the frequency of a component in the PDS changes with energy, namely GRS 1915+105 (Qu et al 2010;Yan et al 2012;van den Eijnden et al 2017;Yan et al 2018), H 1743-322 (Li et al 2013van den Eijnden et al 2017), XTE J1550-564 and XTE J1859+226 (van den Eijnden et al 2017 and MAXI 1535-571 (Huang et al 2018). The behaviour of 𝐿 𝑙 is similar to the one observed for the QPO of MAXI J1535-571 with frequencies above 3 Hz presented in Huang et al (2018).…”
Section: Energy Dependence Of the Fwhm Of 𝐿 𝑙mentioning
confidence: 99%
“…In this state, the source does not show much variability. It also spends a significant amount of time in a highly variable ρ class, also known as the heartbeat class (heartbeat class hereafter), which has been widely studied in the literature (Taam et al 1997;Paul et al 1998;Yadav et al 1999;Neilsen et al 2011Neilsen et al , 2012Pahari et al 2014;Yan et al 2018). The phase-resolved spectroscopy for the heartbeat class was done by Neilsen et al (2012) using RXTE/PCA data in 3.3-45.0 keV band.…”
mentioning
confidence: 99%